Using E-learning standards to move towards Mlearning (Al-Mansour Journal, 2022)
The exploitation of technological advances in learning has result in an exponential progress in this field through e-learning applications in the last decade, and currently through the emergence of a new concept called mlearning.M-learning is defined as the use of mobile technologies for learning; m-learning must benefit from e-learning technological advances in order to avoid reinventing the wheel. Nevertheless, M-learning, which is characterized by the use of mobile devices, permits, for example, the learners' mobility during their learning, and, as opposed to e-learning, allows a continuous change of the context.Moreover, m-learning faces some constraints caused by the use of its mobile technologies such as the limited screen size, reduced energy, resolution capacity and location change during an activity. Yet, there is an agreement among most research laboratories interested in e- and m- learning on the parallel use of these two learning environments.The utilization of standards can offer pedagogical contents some structures which facilitate the interchangeability between e- and m- learning. In order to ensure the interoperability between E- and –M learning platforms and to take into account the specificities of m-learning, we have adopted the already existing standard LOM (Learning Object Metadata) and the specification IMS LD (Interoperability Media Standards –Level Design).
Keywords: m-learning; e-learning; interoperability; LOM; IMS LD